Regulation of xanthine dehydrogensase gene expression and uric acid production in human airway epithelial cells. - Ryan D Huff; Alan C-Y Hsu; Kristy S Nichol; Bernadette Jones; Darryl A Knight; Peter A B Wark; Philip M Hansbro; Jeremy A Hirota (PLoS ONE)
Introduction The airway epithelium is a physical and immunological barrier that protects the pulmonary system from inhaled environmental insults. Uric acid has been detected in the respiratory tract and can function as an antioxidant or damage associated molecular pattern. We have demonstrated that human airway epithelial cells are a source of uric acid. Our hypothesis is that uric acid production by airway epithelial cells is induced by environmental stimuli associated with chronic respiratory diseases. We therefore examined how airway epithelial cells regulate uric acid production. Materials and methods Allergen and cigarette smoke mouse models were performed using house dust mite (HDM) and cigarette smoke exposure, respectively, with outcome measurements of lung uric acid levels. Primary human airway epithelial cells isolated from clinically diagnosed patients with asthma and chronic obstructive pulmonary disease (COPD) were grown in submerged cultures and compared to age-matched healthy controls for uric acid release. HBEC-6KT cells, a human airway epithelial cell line, were grown under submerged monolayer conditions for mechanistic and gene expression studies. Results HDM, but not cigarette smoke exposure, stimulated uric acid production in vivo and in vitro. Primary human airway epithelial cells from asthma, but not COPD patients, displayed elevated levels of extracellular uric acid in culture. In HBEC-6KT, production of uric acid was sensitive to the xanthine dehydrogenase (XDH) inhibitor, allopurinol, and the ATP Binding Cassette C4 (ABCC4) inhibitor, MK-571. Lastly, the pro-inflammatory cytokine combination of TNF-α and IFN-γ elevated extracellular uric acid levels and XDH gene expression in HBEC-6KT cells. Conclusions Our results suggest that the active production of uric acid from human airway epithelial cells may be intrinsically altered in asthma and be further induced by pro-inflammatory cytokines.